Pengembangan Bahan Ajar Fisika Berbasis M-Learning untuk Meningkatkan Akses Belajar Siswa di Era Digital - Shabrina Amalia; Dwitri Pilendia (Peneliti.net, 2022)
This research was conducted based on the results of observations made on physics teachers at SMA N 1 Sungai Penuh. Observation results show that 86% of physics teachers still use teaching materials in the form of printed books that have been provided at school. Some of the difficulties experienced by students are the difficulty of understanding the contents of the available textbooks. This study aims to produce a teaching material that can increase students' access to learning physics in the digital era. Teaching materials are an important part of learning because they can be used as learning resources for both students and teachers. This development research uses a 4D Model adapted from Thiagrajan. After doing the research, the teaching materials in the form of M-Learning are Valid, Practical, and Effective.